Hubungan Tingkat Keparahan Maloklusi dengan Kualitas Hidup Mahasiswa Fakultas Kedokteran Gigi - Eva Novawaty; Yustisia Puspitasari; Wilda N. Bachtiar (e-GiGi, 2024)
Abstract: Malocclusion can cause periodontal problems, dysfunctions in swallowing, chewing, and speaking, as well as psychosocial problems related to aesthetics. Assessment of the severity and need for treatment of malocclusion requires malocclusion index inter alia the Dental Aesthetic Index. Quality of life related to dental and oral health (OHRQoL) is an important parameter for patients, especially in the assessment of almost every field of physical and mental health, including orthodontics. This study aimed to determine the relationship between the severity of malocclusion and the quality of life among students of the Faculty of Dentistry. This was an analytical and observational study with a cross sectional design. Data were analyzed with the Spearman correlation test. Subjects were students of Faculty of Dentistry Universitas Muslim Indonesia that met the requirements. The results obtained 88 students as subjects. Based on sex, the highest frequency of malocclusion was female (81.7%), the highest frequency of malocclusion severity was mild (76.1%), and the highest frequency of quality of life based on OHIP-14 was good (81.8%). The Spearman test showed a p-value of 0.004 for the relationship beween the severity of malocclusion and quality of life. In conclusion, there is a significant relationship between malocclusion and the quality of life among students of Faculty of Dentistry Universitas Muslim Indonesia. Keywords: malocclusion; quality of life; Dental Aesthetic Index; Oral Health Impact Profile- 14.   Abstrak: Maloklusi dapat menyebabkan terjadinya masalah periodontal, gangguan fungsi menelan, pengunyahan, masalah bicara dan psikososial yang berkaitan dengan estetika. Penilaian terhadap tingkat keparahan dan kebutuhan perawatan maloklusi ditentukan dengan indeks maloklusi, salah satunya ialah Dental Aesthetic Index (DAI). Kualitas hidup terkait kesehatan gigi dan mulut (OHRQoL) merupakan parameter penting bagi pasien terutama penilaian di hampir setiap bidang fisik dan mental perawatan kesehatan, termasuk ortodonti. Penelitian ini bertujuan untuk mengetahui hubungan tingkat keparahan maloklusi dengan kualitas hidup mahasiswa Fakultas Kedokteran Gigi (FKG). Jenis penelitian ialah observasional analitik dengan desain potong lintang yang menggunakan uji koelasi Spearman. Subjek penelitian ialah mahasiswa FKG Universitas Muslim Indonesia yang memenuhi kriteria. Hasil penelitian mendapatkan 88 mahasiswa sebagai subjek penelitian. Frekuensi tertinggi yang mengalami maloklusi berdasarkan jenis kelamin ialah perempuan (81,7%), frekuensi tingkat keparahan maloklusi tertinggi ialah maloklusi ringan (76,1%), dan frekuensi kualitas hidup tertinggi berdasarkan OHIP-14 ialah kualitas baik (81,8%). Hasil uji Spearman terhadap hubungan antara tingkat keparahan maloklusi dengan kualitas hidup mendapatkan nilai p=0,004. Simpulan penelitian ini ialah terdapat hubungan bermakna antara maloklusi dengan kualitas hidup mahasiswa Fakultas Kedokteran Gigi Universitas Muslim Indonesia. Kata kunci: maloklusi; kualitas hidup; Dental Aesthetic Index; Oral Health Impact Profile-14